“THE ROLE AND CHALLENGES OF ANALYTICAL THINKING IN ACADEMIC WRITING: A LITERATURE-BASED ANALYSIS” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article investigates the challenges students face in academic writing despite possessing strong English language skills, focusing on the critical role of analytical thinking. It identifies causes of failure in essay writing, including lack of confidence, limited critical evaluation of sources, insufficient background knowledge, and weak argument development. The study emphasizes strategies to overcome these difficulties by employing structured writing methods such as the PEEL (PointEvidence-Explanation-Link) and CER (Claim-Evidence-Reasoning) techniques. Experiments designed to evaluate the efficacy of these methods demonstrate that both PEEL and CER improve clarity, organization, critical thinking, and the overall quality of student essays. The findings suggest that implementing these structured approaches can significantly enhance the academic writing process and strengthen students’ analytical thinking skills.